Speaking in tongues: Family communication in a multicultural society - Ting, Su Hie; Sim, Edmund U. H. (UK: Whiting & Birch, 2015)
Language is an aspect of culture that defines a person, just like how customs and ways of life and beliefs make a person who they are. When two persons get together in a marriage, much accommodation and assimilation of practices, attitudes and values take place so that two different individuals can live together harmoniously. The conjoining of two different lives almost always necessitates a decision on mutual language use, whether this takes place consciously or sub-consciously. While language can bring about ethnic pride, it can also be a factor for societal discord. This can be seen when one ethnic group champions its language at the expense of other ethnic groups. Similarly, in a mixed marriage, language choice can be influenced by ethnic pride. A couple from different cultures may use language to champion their own cultural identity. Another way of explaining ethnic pride here is the notion that languages can be consciously or subconsciously ranked in a hierarchical order as markers of cultural superiority. For instance, an ethnic group that considers itself as being an older civilization often ranks its language as more advanced or superior relative to those from a younger civilization. In an interethnic marriage, language choice can be biased by mindsets that assume civilizational superiority. Although much has been debated on this, there is very little information from empirical studies to support or refute this supposition. Our study is perhaps among the few to boldly address this phenomenon.